Changing Epidemiology of Hepatitis A in China: Evidence From Three National Serological Surveys and the National Notifiable Disease Reporting System. Issue 4 (4th November 2020) - Wang, Fuzhen; Sun, Xiaojin; Wang, Feng; Zheng, Hui; Jia, Zhiyuan; Zhang, Guomin; Bi, Shengli; Miao, Ning; Zhang, Shuang; Cui, Fuqiang; Li, Li; Wang, Huaqing; et al.
Abstract : Background and Aims: China has conducted surveillance for hepatitis A since 1990, and hepatitis A was highly‐to‐intermediately endemic in 1992 when a Chinese hepatitis A vaccine (HepA) was licensed and introduced as a family‐pay vaccine. In 2008, HepA was introduced into the Expanded Program on Immunization as a free childhood vaccine. Approach and Results: Three nationally representative surveys conducted in 1992, 2006, and 2014 assessed hepatitis B serology. The 1992 survey included hepatitis A virus (HAV) serology, and we tested sera from the 2006 and 2014 surveys for HAV antibodies. We used surveillance, seroprevalence, and vaccination status data to describe the changing epidemiology of hepatitis A in China from 1990 through 2014. Before HepA licensure, anti‐HAV seroprevalence was 60% at 4 years of age, 70% at 10 years, and 90% at 59 years; incidence was 52/100, 000 and peaked at 4 years. In 2006, after >10 years of private sector vaccination, HepA coverage was <30% among children <5 years, and incidence was 5.4/100, 000 with a peak at 10 years. In 2014, coverage was >90% among children under 5 years; incidence was 1.9/100, 000. Individuals born before the national introduction of HepA (1988‐2004) had lower anti‐HAV seroprevalence than earlier and later birth cohorts. Conclusions: The incidence of hepatitis A declined markedly following HepA introduction and improvement of sanitation and hygiene. The emerging epidemiology is consistent with disease‐induced immunity having been replaced by vaccine‐induced immunity, resulting in a low incidence of hepatitis A. Catch‐up HepA campaigns to close the immunity gap among the 1998‐2004 birth cohorts should be considered.